2003
DOI: 10.1377/hlthaff.22.3.89
|View full text |Cite
|
Sign up to set email alerts
|

It’s The Prices, Stupid: Why The United States Is So Different From Other Countries

Abstract: This paper uses the latest data from the Organization for Economic Cooperation and Development (OECD) to compare the health systems of the thirty member countries in 2000. Total health spending--the distribution of public and private health spending in the OECD countries--is presented and discussed. U.S. public spending as a percentage of GDP (5.8 percent) is virtually identical to public spending in the United Kingdom, Italy, and Japan (5.9 percent each) and not much smaller than in Canada (6.5 percent). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
278
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 600 publications
(286 citation statements)
references
References 13 publications
7
278
0
1
Order By: Relevance
“…9 In many cases, particularly in the United States, it is high prices, even more than excessive service volume, that really drive massive U.S. health care spending. [10][11][12] But even if we choose to address volume rather than prices and other systematic drivers, cost-sharing ignores the fact that a large amount of overuse is only slightly (and indirectly) driven by patients. After all, patients cannot order their own tests, including costly advanced imaging, or most any therapy, nor have themselves admitted for a massively expensive hospital stay, without at least the agreement of the person most responsible for such decisions -a physician.…”
Section: Paul Atkinsonmentioning
confidence: 99%
“…9 In many cases, particularly in the United States, it is high prices, even more than excessive service volume, that really drive massive U.S. health care spending. [10][11][12] But even if we choose to address volume rather than prices and other systematic drivers, cost-sharing ignores the fact that a large amount of overuse is only slightly (and indirectly) driven by patients. After all, patients cannot order their own tests, including costly advanced imaging, or most any therapy, nor have themselves admitted for a massively expensive hospital stay, without at least the agreement of the person most responsible for such decisions -a physician.…”
Section: Paul Atkinsonmentioning
confidence: 99%
“…A large fraction of the difference between the US share and that of other developed countries (probably more than half although precise measurement here is hard to do) results from that fact that, at exchange rates based on overall purchasing power, medical care prices for many things are much higher in the US than anywhere. But it is even more important to note that the bulk of higher prices (with drugs as a probable exception) are caused by wages for medical workers-physicians, nurses, and even unskilled hospital workers-being higher in America than anywhere else (Pauly 1993;Anderson et al 2003Anderson et al , 2007Laugeson and Glied 2011). The mirror image is that the share of our workforce in health care is not out of line with the share in most developed countries.…”
Section: Medical Spending's Share Of Gdp and Other Useless And Usefulmentioning
confidence: 99%
“…In an international overview of case-mix classification systems in 25 countries, French and colleagues found that DRG and procedure coding varies by country (31). With respect to utilization, wide variations are observed internationally in average hospital lengths of stay (32), which implies either fundamental differences in the health status of different populations, differences in norms about appropriate lengths of stay, differences in the product of a hospital day, or all of the above.…”
Section: Key Considerationsmentioning
confidence: 99%